Implementasi Kepatuhan Syariah pada Produk Simpanan Sembako di KSPPS Artha Yasmin Az Zahra Jepara - Azizah, Wafiq Nur; Anwar, Aan Zainul (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2025)
Islamic Microfinance Institutions play a strategic role in providing financial services that comply with Sharia principles, including through innovative savings products that benefit members. One of the products offered by KSPPS Artha Yasmin Az Zahra Jepara is the Simpanan Sembako (Simko) savings program. Compliance with fatwas and Sharia principles is a crucial factor in maintaining member trust and ensuring the legality of transactions. This study aims to analyze Sharia compliance in the Simko savings product at KSPPS Artha Yasmin Az Zahra, focusing on the issue of implementing Sharia compliance in the practice of Simko. Using a qualitative case study approach, primary data were obtained through direct field research, including interviews with the Manager, members, and the Sharia Supervisory Board (DPS) of KSPPS Artha Yasmin Az Zahra, Jepara Regency. Secondary data were obtained from various sources such as reports, documents, and other materials relevant to the discussion of compliance with Sharia contracts. The results of the study indicate that KSPPS Artha Yasmin Az Zahra has implemented the Simko product in accordance with Sharia principles. The product is free from elements of riba, gharar, and maisir, and is in line with DSN-MUI fatwas regarding Wadiah and savings contracts. Nevertheless, challenges remain in its implementation, particularly regarding members’ understanding of the contract used. This is mainly due to the low level of Sharia literacy among members and the suboptimal socialization efforts from the KSPPS management.